Penerapan Experential Learning pada Materi Trigonometri Peserta Didik Kelas X untuk Meningkatkan Hasil Belajar Peserta Didik - Nabilah Syadza Mahdiyyah (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
Some students feel that mathematics is unnecessary, resulting in their interest in learning being low and learning outcomes also being low. To overcome this, one approach that can be taken is experiential learning. This approach is based on four phases, namely real experience, reflective observation, abstract conceptual, and active experimentation. The four phases involve students in the learning process through acting, reflecting, thinking and applying. The aim of this research is to describe the learning process carried out using an experiential learning approach to trigonometry material to improve student learning outcomes. The research was conducted on 35 class X students. The data collection methods used were tests and field notes. The research results show an increase in student learning outcomes in three aspects, namely student learning completeness which reaches a score of more than or equal to 75, students' activeness in asking questions, arguing and working together in groups, and students' enthusiasm in taking tests given by the teacher. In conclusion, the application of experiential learning in class X trigonometry material can improve student learning outcomes.